”Nej, det er ikke en papegøje”: Et empirisk indblik i koordinationen af tale, blik og peg hos børn i tre-årsalderen - Rohde, Morten (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2019)
Human communication comprises a precise coordination between speech, gaze and gesture. To investigate the rooting of this system in humans, the study of child language development can be a beneficial method. Studies of gradual development of speech, gaze and gesture coordination in children have found that adult-like use of these communication channels is observable from the age of three. Studies investigating the universality of these findings and children’s use of these communication channels to monitor and guide recipients are still to be conducted. This study investigates the development of coordinated multimodal communication and recipient monitoring in Danish children of this age in naturally occurring conversations, and possible explanations for mismatches in verbal and non-verbal communication in children are discussed. It is found that Danish children do exhibit a well-developed use of coordinated multimodal communicated by their third year, but it is also found that a degree of playfulness and lenience in their body language remains. Furthermore, it is found that monitoring of speech recipients by children in this age is highly developed and can be realised by verbal as well as non-verbal tools.